Optimized AIR and investigational MOLLI cardiac T1 mapping pulse sequences produce similar intra‐scan repeatability in patients at 3T. (5th September 2016) - Hong, KyungPyo; Collins, Jeremy; Lee, Daniel C.; Wilcox, Jane E.; Markl, Michael; Carr, James; Kim, Daniel
Abstract: This study was conducted to improve the precision of arrhythmia‐insensitive rapid (AIR) cardiac T 1 mapping through pulse sequence optimization and then evaluate the intra‐scan repeatability in patients at 3T against investigational modified Look–Locker inversion recovery (MOLLI) T 1 mapping. In the first development phase (five human subjects), we implemented and tested centric‐pair k ‐space ordering to suppress image artifacts associated with eddy currents. In the second development phase (15 human subjects), we determined optimal flip angles to reduce the measurement variation in T 1 maps. In the validation phase (35 patients), we compared the intra‐scan repeatability between investigational MOLLI and optimized AIR. In 23 cardiac planes, conventional centric k ‐space ordering (3.7%) produced significantly ( p < 0.05) more outliers as a fraction of left ventricular cavity area than optimal centric k ‐space ordering (1.4%). In 15 human subjects, for each of four types of measurement (native myocardial T 1, native blood T 1, post‐contrast myocardial T 1, post‐contrast blood T 1 ), flip angles of 55–65° produced lower measurement variation while producing results that are not significantly different from those produced with the previously used flip angle of 35° ( p > 0.89, intra‐class correlation coefficient ≥ 0.95 for all four measurement types). Compared with investigational MOLLI (coefficient of repeatability, CR = 40.0, 77.2, 26.5, and 25.9 ms for native myocardial, native blood, post‐contrast myocardial, and post‐contrast blood T 1, and 2.0% for extracellular volume (ECV) measurements, respectively), optimized AIR (CR = 54.3, 89.7, 30.5, and 14.7 ms for native myocardial, native blood, post‐contrast myocardial, and post‐contrast blood T 1, and 1.6% for ECV measurements, respectively) produced similar absolute intra‐scan repeatability in all 35 patients in the validation phase. High repeatability is critically important for longitudinal studies, where the goal is to monitor physiologic/pathologic changes, not measurement variation. Optimized AIR cardiac T 1 mapping is likely to yield high scan–retest repeatability for pre‐clinical and clinical applications. Abstract : This study was conducted to improve the precision of AIR cardiac T1 mapping through k‐space ordering and flip angle optimization. Rigorour evaluation in 35 patients show that investigational MOLLI and optimized AIR produce similar intra‐scan repeatability as shown below. Optimized AIR cardiac T1 mapping is likely to yield high test–retest repeatability for pre‐clinical and clinical applications.